Does team stability mediate the relationship between leadership and team learning? An empirical study among Dutch project teams. Issue 2 (February 2015) - Savelsbergh, Chantal M.J.H.; Poell, Rob F.; van der Heijden, Beatrice I.J.M.
Abstract An exploratory field study was conducted among 30 project teams in the sectors of building and utilities, engineering and construction, infrastructure, and area decontamination and development in the Netherlands. It examined the influence of leadership on team learning behaviors and included team stability as a potential mediator, all analyzed at the team level using structural equation modeling. Results indicated that both person-oriented and task-oriented leadership behaviors were directly and positively related to team learning. Team stability did not mediate the relationship between leadership and team learning; however, a strong direct relationship between team stability and team learning was found. These findings have implications for interventions by all stakeholders of project teams (i.e., team members, project managers, and supervisors) aimed at increasing team learning. Suggestions are presented for leadership practices that stimulate project team learning behaviors.